Noise suppression for MHD characterization with electron cyclotron emission imaging 1D technique. (19th March 2021) - Yu, G; Kramer, G J; Zhu, Y; Li, X; Wang, Y; Diallo, A; Ren, Y; Yu, J H; Chen, Y; Liu, X; Cao, J; Zhao, B; et al.
Abstract: Significant noise suppression for magnetohydrodynamics (MHD) mode characterization in the spatial and spectral domain is achieved by processing two-dimensional (2D) electron cyclotron emission imaging (ECEI) data with a one-dimensional (1D) ECEI technique using a short time window ( 1 ms ). The technique is applied to detect toroidal Alfven eigenmodes (TAEs) in the temporal spectrum and fit their radial envelope using the data from the DIII-D tokamak W-band 2D ECEI system. Using the data length (time window) of only 1 ms, the 1D ECEI can clearly detect the TAEs (∼100 kHz ) on the spectrum, while similar spectrum quality requires ∼10 ms data length with the cross power spectrum between two midplane ECEI channels. The 1D ECEI technique also effectively avoids biased fitting when resolving the fine structure of the TAE's radial envelope. The radially spatial resolution of 1D ECEI is constrained by the finite ECE radiation volume of the ECEI receiver. With forward radiation modeling, we find the DIII-D ECEI system can sensitively measure the even parity MHD activities, for which the mode width is >15 mm, and tearing modes (odd parity MHD activities), for which the island full width is >30 mm.